Elective incisional hernia repair: lower risk of postoperative wound infection with laparoscopic versus open repair - Serene Si Ning Goh; Kaushal Amitbhai Sanghvi; Aaryan Nath Koura; Jaideepraj Krishnaraj Rao; Aung Myint Oo (Singapore Medical Journal)
Introduction: The superiority of laparoscopic repair over open repair of incisional hernias (IHs) in the elective setting is still controversial. Our study aimed to compare the postoperative outcomes of laparoscopic and open elective IH repair in an Asian population. Methods: This retrospective study was conducted in an acute general hospital in Singapore between 2010 and 2015. Inclusion criteria were IH repair in an elective setting, IHs with diameter of 3–15 cm, and location at the ventral abdominal wall. We excluded patients who underwent emergency repair, had recurrent hernias or had loss of abdominal wall domain (i.e. hernia sac containing more than 30% of abdominal contents or any solid organs). Postoperative outcomes within a year such as recurrence, pain, infection, haematoma and seroma formation were compared between the two groups. Results: There were 174 eligible patients. The majority were elderly Chinese women who were overweight. Open repair was performed in 49.4% of patients, while 50.6% underwent laparoscopic repair. The mean operation time for open repair was 116 minutes (116 ± 60.6 minutes) and 139 minutes (136 ± 64.1 minutes) for laparoscopic repair (P = 0.079). Within a year after open repair, postoperative wound infection occurred in 15.1% of the patients in the open repair group compared to 1.1% in the laparoscopic group (P = 0.0007). Postoperative pain, recurrence and haematoma/seroma formation were comparable. Conclusion: Elective laparoscopic IH repair has comparable outcomes with open repair and may offer the advantage of reduced postoperative wound infection rates.